A study on knowledge, attitude and practice regarding health care waste management among health care workers in Devdaha Medical College and Research Institute - Bajracharya, T; Jirel, KB; Acharya, S (Devdaha Medical Journal, 2026)
Introduction: Health care waste is produced by health care activities. It includes needles, body fluids, body parts, pharmaceuticals, radioactive materials, and cytotoxic drugs, which are generated by health care establishments, health-related laboratories, and health research facilities. The aim of the study is to assess the knowledge, attitude, practice and association between knowledge and demographic variables, Practice and demographic variables among health care workers regarding healthcare waste management. Methods: It is a cross- sectional descriptive study, carried out among 78 health care workers at Devdaha Medical College And Research Institute using semi-structured questionnaire among the health care worker. The questionnaire was divided in 4 sections which included, (I) Demographic data, (II) Knowledge, (III) Practice & (IV) Attitude regarding health care waste management. Descriptive statistic and Chi square/Fisher’s exact test were applied, with p<0.05 considered significant. Results: Among the total 78 participants 91% were female 74% were nurses. Only 32% had received formal training. Nearly half (47%) had moderate knowledge, 42% had right knowledge. Most respondents (85%) demonstrated neutral attitude, 85% reported good practices regarding health care management. No statistically significant association was found between knowledge level and demographic variables (p>0.05). Practice level showed a statistically significant association with educational qualification (p<0.001). Conclusion: Although health care workers demonstrated good waste management practices, gaps in knowledge and attitude were identified. Regular training, monitoring and reinforcement of institutional guidelines are recommended to strengthen health care waste management service.